2020
DOI: 10.24912/jmieb.v4i2.8402
|View full text |Cite
|
Sign up to set email alerts
|

Keterhubungan Antara Kemampuan, Kebajikan (Benevolence), Dan Integritas Perusahaan Terhadap Kepercayaan Dan Partisipasi Pelanggan: Studi Empiris Pada Tokopedia

Abstract: Penelitian ini bertujuan untuk memprediksi keterhubungan antara kemampuan, kebajikan, dan integritas Tokopedia terhadap kepercayaan dan partisipasi pelanggan Tokopedia. Sebanyak 130 responden terlibat dalam penelitian ini. Kueioner dikembangkan berdasarkan indikator-indikator penelitian sebelumnya. Skala Likert 5 poin digunakan dalam kuesioner tersebut. Sebelum data dianalisis dengan menggunakan structural equation modeling, data terlebih dahulu diuji reliabilitas dan validitasnya. Hasil analisis menunjukkan b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…This is in line with previous research (Gunarso et al, 2020)which showed that the ability and integrity of the company are the main factors that are closely related to customer trust and participation. Therefore, companies need to continue to maintain and improve their ability to serve consumers while still focusing on the integrity of the company.…”
Section: Integritysupporting
confidence: 93%
See 1 more Smart Citation
“…This is in line with previous research (Gunarso et al, 2020)which showed that the ability and integrity of the company are the main factors that are closely related to customer trust and participation. Therefore, companies need to continue to maintain and improve their ability to serve consumers while still focusing on the integrity of the company.…”
Section: Integritysupporting
confidence: 93%
“…Therefore, companies need to continue to maintain and improve their ability to serve consumers while still focusing on the integrity of the company. Thus, consumers will then continue to trust and maintain their participation (Gunarso et al, 2020). Integrity is very important in banking because it helps generate the trust that is the determinant for the financial system to thrive (Cowton, 2002).…”
Section: Integritymentioning
confidence: 99%
“…Although previous interactions do not guarantee that the bank's service will be as expected by the customer, customer confidence will increase if the bank previously provided services that were in line with expectations. The dimensions of customer trust in this study consist of:  Integrity This is in line with previous research [15] which showed that the ability and integrity of the company are the main factors that are closely related to customer trust and participation. Therefore, companies need to continue to maintain and improve their ability to serve consumers while still focusing on the integrity of the company.…”
Section: Customer Trustsupporting
confidence: 86%
“…Therefore, companies need to continue to maintain and improve their ability to serve consumers while still focusing on the integrity of the company. Thus, consumers will then continue to trust and maintain their participation [15]. Integrity is very important in banking because it helps generate the trust that is the determinant for the financial system to thrive [16].…”
Section: Customer Trustmentioning
confidence: 99%
“…Next is netnographic research methods which used in the subsequent investigation, which examines how virtual communities can act as message and opinion makers in a tourism platform and how this can play an essential role in people making decisions or making choices when seeking information before traveling (Gunarso et al, 2020). Some theories were used in this research, including the Computer-Mediated Communication (CMC) theory, which is concerned with communication mediated by technology and involves using a symbolic representation system.…”
Section: Introductionmentioning
confidence: 99%